The first record of genus Gryllomorpha Fieber in Romania (Orthoptera: Gryllidae: Gryllomorphinae) - Iorgu, Ionuț Ștefan; Chobanov, Dragan; Skolka, Marius; Zaharia, Răzvan; Iorgu, Elena Iulia (Zootaxa, 2019)
Although the fauna of Dobrogea (south-eastern Romania and north-eastern Bulgaria) is relatively well studied, the discovery of a crevice cricket was quite unexpected. Described from Ukraine and known to occur in Bulgaria, Greece, Turkey, Kazakhstan and possibly Uzbekistan, Gryllomorpha miramae is now recorded for the first time in Romania.